ANALISIS PERTUMBUHAN KREDIT DAN TINGKAT RISIKO KREDIT BERMASALAH PADA BANK BUMN PERIODE 2018-2021 - Virgia Aulia Dewi (2022)
Credit is the provision of money or claims, based on an agreement or loan agreement between the bank and the customer and requires the customer to pay off the debt after a specified period of time with interest. Credit is one of the main activities of banks and is the main source of income for banks. The amount of credit disbursed will determine the bank's profit. The intermediation function that runs well is indicated by good credit growth, because credit growth is seen from the large level of demand for credit by debtors to banks. Good credit distribution by banks can encourage economic growth and development of a country because it can facilitate various parties in carrying out their business activities, especially for companies, government and private agencies, and the community in order to meet their needs. In carrying out its activities, banks do not escape from credit problems. Non-performing loans (NPLs) show the collectability of banks in collecting back loans that have been disbursed by banks. The higher the NPL level indicates that the bank is not good at managing its credit and the public assumes that the risk level of the bank's lending is quite high.